Language planning from practice to theory - Kaplan, Robert B. (Multilingual matters (Series), 1997)
"Language Planning from Practice to Theory examines and reviews the field of language policy and planning. In the first section of the book language policy and planning definitions, current practices, goals and ways of thinking are discussed as a foundation for understanding current practice in the discipline. The central elements of language policy and planning practice are then described from two perspectives. In the second section, the methodology for collecting language planning data is outlined and the key cross-societal issues of language-in-education planning, literacy and economics in language planning are discussed. In the third section, case studies related to language and power, bilingualism and status and specific purpose issues in language planning are covered. The final two chapters draw together the critical issues and problems which have arisen from current practice and which must be considered in building a theory of the discipline. A reference appendix to language planning in national situations is included." "The book provides the only up-to-date overview and review of the field of language policy and planning and challenges language planners to think more critically about their discipline. Since language will be planned, there is a need to consider how it will be done."--Jacket.